2019
DOI: 10.1039/c9dt00452a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of aminopyridine iron(ii) chloride catalysts for isoprene polymerization: sterically controlled monomer enchainment

Abstract: Aminopyridine iron(ii) chloride complexes coordinating a type of flexible ligand are reported as precursors for controlled polymerization of isoprenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 68 publications
1
26
0
Order By: Relevance
“…In the past few months, the same research group disclosed the polymerization of isoprene using a series of iron-based complexes supported by aminopyridine ligands (Figure 2(D)) [28]. Upon activation with an excess of MAO, these pre-catalysts provided a wide range of polyisoprene microstructures with, in most cases, high content of 3,4 units.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few months, the same research group disclosed the polymerization of isoprene using a series of iron-based complexes supported by aminopyridine ligands (Figure 2(D)) [28]. Upon activation with an excess of MAO, these pre-catalysts provided a wide range of polyisoprene microstructures with, in most cases, high content of 3,4 units.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, when the IP/Fe ratio was increased to 10000, although the conversion of monomer was reduced, the activity was improved to 2.34 × 10 6 g polymer mol –1 h –1 within 10 min (Table , entry 11), which indicated that the capacity of Fe- i Pr -catalyzed isoprene polymerization was superior to that of secondary aminopyridine iron­(II) complexes with a maximum value of 1.9 × 10 6 g polymer mol –1 h –1 previously reported . Next, the Al/Fe ratio was investigated (Table , entries 12 and 13).…”
Section: Results and Discussionmentioning
confidence: 90%
“…Thus, the electrophilic aminopyridine iron center (LFe 2+ ) tends to coordinate with the incoming monomer through cis -η 4 mode rather than η 2 mode (Scheme ). , In addition, the 1,4-regularity is generated via the active iron center bound to the C1 position of anti -η 3 or syn -η 3 allyl intermediates, while 3,4-regularity is achieved though the active iron center bound to the C3 position . When the iron center is bound to the C1 position via syn -η 3 allyl intermediates, isomerized by the anti -η 3 -allyl intermediates, the trans -1,4-regularity would become visible.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations